Sensitive Detection of Thirteen Bacterial Vaginosis-Associated Agents Using Multiplex Polymerase Chain Reaction - Malaguti, Natália (Biomed Res Int, 2015)
Bacterial vaginosis (BV) is characterized by a polymicrobial proliferation of anaerobic bacteria and depletion of lactobacilli, which are components of natural vaginal microbiota. Currently, there are limited conventional methods for BV diagnosis, and these methods are time-consuming, expensive, and rarely allow for the detection of more than one agent simultaneously. Therefore, we conceived and validated a multiplex polymerase chain reaction (M-PCR) assay for the simultaneous screening of thirteen bacterial vaginosis-associated agents (BV-AAs) related to symptomatic BV: Gardnerella vaginalis, Mobiluncus curtisii, Mobiluncus mulieris, Bacteroides fragilis, Mycoplasma hominis, Atopobium vaginae, Ureaplasma urealyticum, Megasphaera type I, Clostridia-like bacteria vaginosis-associated bacteria (BVABs) 1, 2, and 3, Sneathia sanguinegens, and Mycoplasma genitalium. The overall validation parameters of M-PCR compared to single PCR (sPCR) were extremely high, including agreement of 99.1% and sensitivity, specificity, and positive predictive values of 100.0%, negative predictive value of 97.0%, accuracy of 99.3%, and agreement with Nugent results of 100.0%. The prevalence of BV-AAs was very high (72.6%), and simultaneous agents were detected in 53.0%, which demonstrates the effectiveness of the M-PCR assay. Therefore, the M-PCR assay has great potential to impact BV diagnostic methods in vaginal samples and diminish associated complications in the near future.